Engineering in Mathematics Education: Mathematical Engineering - Chaurasia, Praveen Kumar (JOURNAL OF INDIAN EDUCATION, 2009)
We all have our own experiences of Mathematics since our very early childhood. Most of us have developed our own understanding of learning of mathematics. Through this article, the author appeals for a self-analysis of our understanding of learning and teaching Mathematics. The focus of this article is largely devoted to supporting the improvement of mathematics teaching and learning and ultimately the performance of students on measures of mathematics achievement. This article is written with the hope that it will help the reader understand how researchbased strategies can support the engineering of positive change to the structures supporting the teaching and learning of mathematics in educational settings. Basically, main emphasis will be on the engineering set up in mathematics education. The entire findings are based on discussion on mathematics of concept of “fraction”. “Mathematics—I want to say—teaches you, not just the answer to a question, but a whole language-game with questions and answers”.